Nursing Care In Health Care Facilities According To Law No. 17 Of 2023 - Jahidin Kuswanto; Widjaja, Gunawan (Jurnal Indonesia Sosial Sains, 2025)
Health as one aspect of human rights is recognized and protected by the State through the provisions of Article 28 H paragraph (1) of the 1945 Constitution, which emphasizes that every individual has the right to adequate health services. Nursing personnel have a very important role in creating quality health services, both in primary health facilities and in implementing individual and community health efforts, which is the form of health service that is closest to the community as the first contact in Health Services. In addition, nurses also play a role in nursing care in advanced health care facilities with a bio-psycho-social-cultural-spiritual approach. This study aims to explain Nursing Care in Health Facilities in terms of Law No. 17 of 2023. This study is a basic research with an analytical descriptive approach . The results of this study show no difference in the implementation of Nursing Care carried out in Primary Health Facilities (FKTP) and Advanced Health Facilities (FKTL).